Characterizing formations with well tests [kasetvideo] : modules 1-5 - 188655 Lee, W. John; Society of Petroleum Engineers (United States) (SPE, 1986)
Module 1. Examining fluid flow in porous media -- Module 2. Analyzing oil well buildings tests -- Module 3. Analyzing multiphase and gas well buildings tests -- Module 4. Analyzing flow tests -- Module 5. Evaluating formations after fracturing